Immunohistochemical Expression and Localization of Somatostatin Receptor Subtypes in Androgen Ablated Prostate Cancer - Roberta Mazzucchelli; Doriana Morichetti; Alfredo Santinelli; Marina Scarpelli; Aldo V. Bono; Antonio Lopez-Beltran; Liang Cheng; Rodolfo Montironi (Analytical Cellular Pathology)
Objective: The aim was to examine the expression and localization of the five somatostatin receptors (termed SSTR1–5) in radical prostatectomies (RPs) from patients with prostatic adenocarcinoma (PCa) under complete androgen ablation (CAA) before operation.